ANDROID-BASED RADIATION DOSE RISK EDUCATION MODEL - Supriyani, Nyoman; Anwar, M. Choiroel; Katili, Irwan (Postgraduate Program , Poltekkes Kemenkes Semarang, 2020)
Background: The risk of radiation doses for patients undergoing radiological examinations can have somatic and genetic effects. Somatic effects are effects that are directly felt by patients, while genetic effects arise due to damage to DNA molecules in the long run. Providing appropriate education is an effort to prevent the risk of radiation doses. If the education model is only verbal, the potential for misinformation is also very large. Submission of misinformation certainly has implications for the risk of repeat examinations and in turn provides even more radiation doses for patients. In response to this, the development of an android application based education model is very much needed.Method: This type of research is a Research and Development (R&D) research. The research design is quasy experiment pre post test control group design with a total sample of 45 patients. Data collection tools using the e-3Ramed application, questionnaires and questionnaires. Univariate analysis produces frequency distributions of respondents' characteristics. Bivariate analysis produces the effect of educational interventions on increasing the knowledge and attitudes of radiology patients about the risk of radiation doses by the McNemar and Kruskal Wallis tests.Results: All educational models were effective in increasing the knowledge and attitudes of radiology patients about the risk of radiation doses with a p-value <0.05. But the most effective educational model and has the highest ranking value is a combination of oral and android with a mean rank of 29.07.Conclusion: An Android-based educational model has been developed, the e-3Ramed application which is effective in increasing the knowledge and attitudes of radiology patients about the risk of radiation doses.Keywords: Education, Risk of Radiation Dose, e-3Ramed Latar Belakang: Risiko dosis radiasi bagi pasien yang melakukan pemeriksaan radiologi dapat menimbulkan efek somatik dan efek genetik. Efek somatik adalah efek yang langsung dirasakan pasien, sedangkan efek genetik timbul karena kerusakan molekul DNA dalam jangka panjang. Pemberian edukasi yang tepat merupakan upaya pencegahan risiko dosis radiasi tersebut. Bila model edukasinya hanya bersifat lisan saja maka potensi kesalahan penyampaian informasi juga sangat besar. Penyampaian informasi yang salah tentu berimplikasi pada risiko pengulangan pemeriksaan dan pada gilirannya memberi dosis radiasi yang lebih banyak lagi bagi pasien. Menyikapi hal itu, pengembangan model edukasi berbasis aplikasi android sangat diperlukan.Metode: Jenis penelitian ini merupakan penelitian Research and Development (R&D). Desain penelitiannya yaitu quasy experiment pre post test control group design dengan jumlah sampel sebanyak 45 pasien. Alat pengumpulan data menggunakan aplikasi e-3Ramed, kuesioner dan angket. Analisis univariat menghasilkan distribusi frekuensi karakteristik responden. Analisis bivariat menghasilkan pengaruh intervensi edukasi terhadap peningkatan pengetahuan dan sikap pasien radiologi tentang risiko dosis radiasi dengan uji McNemar dan Kruskal Wallis.Hasil: Semua model edukasi efektif meningkatkan pengetahuan dan sikap pasien radiologi tentang risiko dosis radiasi dengan p-value <0,05. Namun model edukasi yang paling efektif dan memiliki nilai rangking tertinggi yaitu kombinasi lisan dan android dengan mean rank 29,07.Kesimpulan: Telah dikembangkan model edukasi berbasis android yaitu aplikasi e-3Ramed yang efektif dalam meningkatkan pengetahuan dan sikap pasien radiologi tentang risiko dosis radiasi.Kata Kunci: Edukasi, Risiko Dosis Radiasi, e-3Ramed